6x+6+7(x+1)=6x+3

Simple and best practice solution for 6x+6+7(x+1)=6x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+6+7(x+1)=6x+3 equation:


Simplifying
6x + 6 + 7(x + 1) = 6x + 3

Reorder the terms:
6x + 6 + 7(1 + x) = 6x + 3
6x + 6 + (1 * 7 + x * 7) = 6x + 3
6x + 6 + (7 + 7x) = 6x + 3

Reorder the terms:
6 + 7 + 6x + 7x = 6x + 3

Combine like terms: 6 + 7 = 13
13 + 6x + 7x = 6x + 3

Combine like terms: 6x + 7x = 13x
13 + 13x = 6x + 3

Reorder the terms:
13 + 13x = 3 + 6x

Solving
13 + 13x = 3 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
13 + 13x + -6x = 3 + 6x + -6x

Combine like terms: 13x + -6x = 7x
13 + 7x = 3 + 6x + -6x

Combine like terms: 6x + -6x = 0
13 + 7x = 3 + 0
13 + 7x = 3

Add '-13' to each side of the equation.
13 + -13 + 7x = 3 + -13

Combine like terms: 13 + -13 = 0
0 + 7x = 3 + -13
7x = 3 + -13

Combine like terms: 3 + -13 = -10
7x = -10

Divide each side by '7'.
x = -1.428571429

Simplifying
x = -1.428571429

See similar equations:

| x(x+1)+29=x+(x+1) | | x^3-2x^2-8=0 | | 2x+123=-78-7x | | x(x+1)=306 | | 26=6+37t-16t^2 | | -24=3b-9 | | 32x(x+2)=11520 | | 9x+6x=60 | | -68x+40+12x^2=0 | | 0.06*w=3.1 | | 8(t-2)+4t=4(3t+3)-9 | | 14v+16=2(5+7v)-4 | | 13a+26=-13 | | 9=-5x+4 | | 2(4z+8)-16=-1.5(9z-12) | | 2x^2+18=15x | | 13=7+21x-16x^2 | | -2f=32 | | 196000=.49*w | | x^3+2x+4x^2+8=0 | | 1024=0.08*w | | -x-y=-2 | | 1.122=p*37.4 | | 178.20=.405*w | | 4v-3(v-2)=13 | | 1.05*w=51.03 | | 1.5(4z+8)-16=-2.3(9z-12) | | .45*w=108 | | 2x-2y+z=-7 | | 4t+3-5t=9 | | -6(y+2)-(-5y-3)=-1 | | 2x-12=-3+x |

Equations solver categories